THE INFLUENCE OF YELLOW RICE PRODUCT QUALITY ON CUSTOMER PURCHASE DECISIONS AT WAROENG KEMBAR BUSINESS IN BARRU REGENCY - Jumriani Jumriani; Agus Syam, Asmayanti, Nur Halim, Marhawati (CV. Adiba Aisha Amira, 2025)
The research aims to determine the effect of product quality on purchasing decisions at the Waroeng Kembar business in Barru Regency.The independent variable in this study is the purchasing decision, and the dependent variable is product quality.The population in this study is all customers of Waroeng Kembar, with a sample size of 90 respondents.Data collection was carried out by distributing questionnaires to the respondents.The analysis method used is simple linear regression analysis using SPSS software.Based on the results of the regression analysis, a significance value of 0.000 was obtained, which is less than 0.05, and the coefficient is positive, thus it can be concluded that product quality positively and significantly affects customer purchasing decisions at Waroeng Kembar.